WILLINGNESS TO WALK STUDY BASED ON WALKING DISTANCE AND PEDESTRIAN FACILITIES CONDITION - NURHALIMA R. M, DESTRI
Pedestrian access and the walking environment are the main things that need to be considered to stimulate the public to use public transport and the mode of walking on short distance trips. If pedestrian facilities are not provided properly, the community will be less interested in walking. Understanding of people's willingness to walk is needed so that any intervention to improve willingness to walk as part of sustainable transportation and development can be right on target. The research was conducted to develop a willingness to walk model for the purpose of college travel and grocery shopping based on the distance that must be taken and the conditions of pedestrian facilities available. In addition, there are sub-objectives of this research, namely to identify the attributes of the conditions of pedestrian facilities that affect the decision to walk. The model used in this study is ordinal logistic regression with input data derived from stated preference survey results. The results show that walking distance, shade availability, surface conditions, cleanliness, crossing, and crowdedness of walking environment influence the willingness to walk to campus (college) and market (grocery shopping). There is a trade off between the walking distance and the condition of pedestrian facilities to the willingness to walk. At the same probability individuals will be willing to walk further on conditions of good pedestrian facilities or will walk shorter to conditions of poor pedestrian facilities. Related to travel purpose, people tend to be willing to go further for the purpose of shopping trips compared to the purpose of college trips.